Forensic Analysis Of Dana Applications Using The ACPO Framework - Ermin, E; Setyawan, Muhammad Rizki; Tella, Fitriyani (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The DANA application is a digital wallet platform designed to make all transactions easier, faster and safer, both online and offline. However, apart from the benefits provided, digital wallet applications can also cause harm to their users, namely negative use which can lead to cybercrime cases. Digital forensics is a branch of forensic science that focuses on investigating and finding digital evidence in cybercrime cases. This study aims to conduct a forensic analysis of the DANA application to identify artifacts that have the potential to be used as digital evidence of cybercrime by using the ACPO framework with the assistance of forensic tools such as the Belkasoft Evidence Center and MobilEdit Forensic Express Pro. Based on the research that has been done, it can be concluded that the use of the ACPO Framework to find out the artifacts obtained can be used properly and forensic analysis of the results obtained using two forensic tools, namely the Belkasoft Evidence Center failed to find artifacts that can be used as digital evidence, while the MobilEdit Forensic tool Express Pro only managed to find artifacts in the form of user photos and screenshots of transactions made..